ANALYSIS ON THE SIZE OF TOURISTIC RECEPTION STRUCTURES FROM THE ALBA COUNTY - GHERGHINA LILIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
The paper Analysis on the size of the touristic reception structures in Alba County, presents an analysis of both the structures with accommodation functions and the structures with public catering functions. Through this study, we found that Alba County has a considerable number of spaces and locations in touristic reception structures with accommodation functions such pensions, guesthouse, hotel, rooms for rent, motel, touristic villa, agrotourism pension, Chalets and hostel. The number of places in structures as: urban / rural boarding house, bungalow, and camping houses, camping spaces and tourist stops is lower. At the level of the Alba County, the public catering structures, depending on the number of places available per type of unit, are mostly classic restaurants and pension restaurants, followed by buffet bars, day Bars and wineries. The fish restaurant, the self-service restaurant, the fast food and the bistro are just a typical unit, with a small number of seats at the table. In the Albac and Arieșeni Resorts the structures of tourist accommodation type Tourist pension predominate, together with agrotourism pensions, rooms for rent, tourist villas, tourist guesthouses, camping cottages, as well as the structures of tourist catering like: classic restaurants, fish restaurant and pension restaurant, day bars and buffet-bars. The existence of an optimal natural and anthropic tourist potential but also of the endowments from the accommodation and public alimentation structures available in Alba County leads to the increase of the tourist flows, respectively of consumption.